RISIKO KEUANGAN DAN TINGKAT KESEHATAN KEUANGAN BANK DENGAN SIZE, INFLASI, DAN GDP SEBAGAI VARIABEL KONTROL PADA PERBANKAN SYARIAH DI INDONESIA - Yuwita Ariessa Pravasanti (ITB AAS INDONESIA Surakarta, 2017)
This study aims to analyze the financial risk and health financial level of banks on Islamic banking in Indonesia. This study aims to get empirical evidence about the possibility of relationship and influence of financial risks (liquidity risk (Financing to Deposit Ratio), financing risks (Non Performing Financing) and operational risk (RWA for operational risk) and the financial soundness of banks (Net Operating margin, Return on Assets and Return on Equity) with the size of bank, inflation and Gross Domestic Product (GDP) as a control variable in islamic banking in Indonesia. This study used panel data analysis and used 9 islamic bank with 5 years in a period, from 2010 to 2014 so the sample used in this study were 45 data. The data were processed using Microsoft Excel and Eviews software version 8.The results showed that simultaneously financial risk not significant effect on NOM, but significant effect on ROA and ROE. Partially NPF variables only significantly influence on NOM, FDR and NPF variable significant effect on ROA, and FDR variable significant effect on ROE. The control variables used in this study had no effect on health financial level.